2012
DOI: 10.2478/v10172-012-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mechanical alloying process on the sintering behaviour of astaloy CrM powder mixture with silicon carbide addition

Abstract: Due to an excellent combination of toughness and strength, bainitic-austenitic dual phase steels with silicon addition have many applications in the industry. However, silicon has a high affinity to oxygen and, therefore, its introduction to the alloy is problematic during the classical sintering processes of mixing powders. Mechanical alloying (MA) offers one of the most attractive alternatives to the introduction of silicon to Astaloy CrM powders.The aim of the present study was to determine the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…Based on all of the obtained results, it may be observed that using an inert atmosphere with 10 % H 2 is enough to obtain the same results as after sintering in a reducing atmosphere of hydrogen. These observations are in accordance with results obtained in previous research [18].…”
Section: Resultssupporting
confidence: 83%
“…Based on all of the obtained results, it may be observed that using an inert atmosphere with 10 % H 2 is enough to obtain the same results as after sintering in a reducing atmosphere of hydrogen. These observations are in accordance with results obtained in previous research [18].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, the mechanical alloying parameters (primarily the ratio of powder mass to ball mass, milling time, size of grinding balls and rotary speed) had a significant effect on the final size of the particles obtained after the alloying process. The obtained results are in full agreement with the results obtained for similar mechanical alloyed compositions which are characterized by the same alloying model -a ductile/brittle component system [21,22].…”
Section: Resultssupporting
confidence: 82%
“…A change or failure to follow them usually results in an abnormality of the constructed product. In powder metallurgy two of the most important technological parameters are adequate atmosphere and sintering temperature [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%